Commercially available carbohydrate drink with menthol fails to improve thermal perception or cycling exercise capacity in males - Podlogar, T.; Bolcic, T.; Cirnski, S.; Verdel, N.; Debevec, T. (European Journal of Sport Science, 2022)
The purpose of this double-blinded, crossover randomized, and counterbalanced study was to compare effects of ingesting a tepid commercially available carbohydrate-menthol containing sports drink (Menthol) and an isocaloric carbohydrate-containing sports drink (Placebo) on thermal perception and cycling endurance capacity "in a simulated home virtual cycling environment". It was hypothesized that addition of menthol would improve indicators of thermal perception and improve endurance exercise capacity. Twelve healthy, endurance-trained males (age 29 ± 5 years, height 181 ± 6 cm, body mass 79 ± 2 kg and V O2max 57.3 ± 6.4 mL · kg-1 · min-1) completed two experimental trials on a stationary bicycle without external air flow. Each trial consisted of 1) cycling for 60 minutes at 90% of the first ventilatory threshold while receiving a fixed amount of Menthol or Placebo every 10 minutes followed immediately by 2) cycling until volitional exhaustion (TTE) at 105% of the intensity corresponding to the respiratory compensation point. TTE did not differ between both conditions (541 ± 177 and 566 ± 150 seconds for Menthol and Placebo; p>0.05) and neither did ratings of perceived thermal comfort or thermal sensation (p>0.05). Also, rectal temperature at the end of TTE was comparable between Menthol and Placebo trials (38.7 ± 0.2 °C and 38.7 ± 0.3 °C, respectively; p>0.05). The present results demonstrate that the addition of menthol to commercially available sports drink does not improve thermal comfort or endurance exercise capacity during ~65 min of intense virtual cycling.